Nilai Sosial dalam Novel Selembar itu Berarti Karya Suryaman Amipriono - Hakimah, Ummie; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Social value is something that becomes a measure and assessment of the appropriateness of an attitude aimed at social life. Social values function as a reference for behavior in interacting with others so that their existence can be accepted in society. The problems studied in this study are (1) What are the social values related to the value of love in the novel Selembar it Means by Suryaman Amipriono?, (2) What are the social values related to the value of responsibility in the novel Selembar itu Means by Suryaman Amipriono? , (3) What are the social values related to the value of harmony in life in the novel Selembar It Means by Suryaman Amipriono? The purpose of this research is to collect, describe, analyze, and interpret data about social values related to the value of affection, the value of responsibility, and the value of harmony in life in the novel Selembar itu Mean by Suryaman Amipriono. The main theory that the author uses is Zubaedi's theory (2012). The method used is descriptive method. The data collection technique used is the hermeneutic technique. The data analysis technique that the writer uses is content analysis technique. The results of research on social values in the novel Selembar itu Means by Suryaman Amipriono, there are 47 data consisting of 23 data on the value of affection shown by the characters Mrs. Hera, Putri, Mrs. Imah, Arya, Nisa, Mrs. Reni, Pak Wildan, and Atri,15 data on the value of responsibility shown by the characters Putri, Mrs. Hera, Pak Lingga, Diaz, Arya, Nisa, Atri, Mrs. Imah, and Mrs. Lina, and 9 data on the value of harmony in life shown by the characters Diaz, Putri, Pak Lingga, Mrs. Imah , Nisa, Mr. Azwar, and Mr. Wildan. Social value in the novel Selembar itu Means by Suryaman Amipriono describes an attitude and action in social life which can be seen from the value of compassion, the value of responsibility, and the value of harmony in life.